Starch-based nanoparticles as a replacement for synthetic latex: A comprehensive assessment of printability and colorimetric characteristics - AYDEMİR, CEM (My University, 2024)
The papermaking, packaging, and printing industry are actively seeking sustainable material alternatives to address growing concerns about environmental consciousness and finite resources. Synthetic latex, a frequently utilized binder in paper coating formulations, present difficulties due to their dependence on fossil fuel resources and their reduced recyclability in comparison to eco-friendly sustainable products. In this study, synthetic latex was replaced with a starch-based nanoparticle (starch NP) binder at a 1:1 ratio in a coating formulation. Printing trials to assess colorimetric characteristics was made using electrophotography (EP) printing, given the current upward trajectory and expansion of EP technology into the label, packaging, and folding carton sectors. The in-depth investigations reveal that incorporating starch NP binder result in improved optical, color, and dot characteristics. Moreover, it maintains consistent and comparable coefficients of friction. Partial replacement of synthetic latex with the starch NP binder yields significant enhancements in surface roughness and text quality. Importantly, the starch NP binder not only improves the dielectric relaxation properties of the paper and enhances toner transfer but also accelerates the distribution of the electrical field compared to synthetic latex, optimizing toner transfer and thereby enhancing color gamut volume. The study demonstrates that employing the starch NP binder leads to substantial improvements in colorimetric performance without any drawbacks in EP printing, making it highly advantageous to replace 50% of the synthetic binder.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Kimya Mühendisliği ve Teknolojisi; Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Chemical Engineering and Technology; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Sosyal Bilimler (SOC); Mühendislik; Sosyal Bilimler Genel; MÜHENDİSLİK, KİMYASAL; ERGONOMİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Social Sciences (SOC); ENGINEERING; CHEMISTRY; SOCIAL SCIENCES, GENERAL; ENGINEERING, CHEMICAL; ERGONOMICS; İnsan Faktörleri ve Ergonomi; Sosyal Bilimler ve Beşeri Bilimler; Genel Kimya; Fizik Bilimleri; Genel Kimya Mühendisliği; Human Factors and Ergonomics; Social Sciences & Humanities; General Chemistry; Physical Sciences; General Chemical Engineering; binder; coating; color; electrophotography; latex; nanoparticle; printing; starch; styrene; toner